Pengembangan Media Buku Teks Subtema Peristiwa Kebangsaan Seputar Proklamasi dengan Penguatan Karakter Cinta Tanah Air Kelas V SD - Agnes Fitri Ayu Wulandari; M. Zainuddin; Tri Murti; Agnes Fitri Ayu Wulandari; M. Zainuddin (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: The purpose of this study is to produce a textbook on the sub-theme of National Events Around the Proclamation by strengthening the character of love for the homeland class V SDN Rejomulyo which is valid according to material experts, media and teachers and is practical for students. This development research uses the ADDIE model. Product validity according to material experts is 95,83 percent, media is 95,83 percent and users are 91,66 percent. The resylts of the initial trial for thr ptacticality assessment obtained a score of 88,33 percent.. While the final trial score 90 percent practicality. So this book is very valid and practical and has a very strong strengthening of the character of love for the homeland. Abstrak: Tujuan penelitian ini menghasilkan buku teks subtema peristiwa kebangsaan seputar proklamasi dengan penguatan karakter cinta tanah air kelas V SDN Rejomulyo  yang valid menurut ahli materi, media, dan  guru serta praktis bagi siswa. Penelitian pengembangan ini menggunakan model ADDIE. Validitas produk menurut ahli materi 95, 83 persen, media  95,83 persen dan pengguna 91, 66 persen. Hasil uji coba awal untuk penilaian kepraktisan memperoleh skor 90 persen. Sedangkan uji coba akhir skor kepraktisan 91,56 persen. Jadi buku ini sangat valid dan praktis serta memiliki penguatan karakter cinta tanah air yang sangat kuat.etode, serta hasil penelitian.